Qualitative Model of the Causal Interactions between Phytoplankton, Zooplankton, and Environmental Factors in the Romanian Black Sea - Elena Bișinicu; Laura Boicenco; Elena Pantea; Florin Timofte; Luminița Lazăr; Oana Vlas (Phycology, 2024)
In order to analyze how environmental factors affect planktonic organisms along the Romanian Black Sea coast, this study created semi-quantitative models of the causal relationships between phytoplankton, zooplankton, and physicochemical parameters by utilizing user-friendly modeling tools. Eleven years of time-series data (March–September 2008–2018) were used to investigate the relationships between phytoplankton, zooplankton, and environmental factors (such as temperature, salinity, and nutrients). Variables such as marine reporting units and phytoplankton species and classes were used to identify developmental patterns, utilizing the Mental Modeler platform to consider interactions between the physicochemical parameters and phytoplankton, phytoplankton and zooplankton, and zooplankton and physicochemical parameters. Although the increase in the overall number of elements and linkages was uncertain in waters with variable salinity compared to marine ones, the semi-quantitative models created for the three marine reporting units along the Romanian Black Sea coast were comparable in terms of complexity. Across the typical and examined types of phytoplankton proliferation (normal, abundant, and blooms), the number of components and connections in the case of phytoplankton blooms substantially decreased as species- and growth-promoting variables increased.